Surgical Effectiveness of Uniportal-VATS Lobectomy Compared to Open Surgery in Early-Stage Lung Cancer - Nachira, Dania; Congedo, Maria Teresa; Tabacco, Diomira; Sassorossi, Carolina; Calabrese, Giuseppe; Ismail, Mahmoud; Vita, Maria Letizia; Petracca-Ciavarella, Leonardo; Margaritora, Stefano; Meacci, Elisa (Frontiers in Surgery, 2022)
BACKGROUND: If feasibility and safety of Uniportal-VATS have been proven, the surgical effectiveness is still debated. The aim of this study is to assess the equivalence of Uniportal-VATS approach compared to open technique in terms of surgical (nodal-upstaging, complications and post-operative results) and short-term survival outcomes. METHODS: Clinical data of patients undergone lobectomy for NSCLC at our center, from January 2014 to December 2019, were analyzed retrospectively. All patients undergone open or Uniportal-VATS lobectomy with lymphadenectomy for an Early-stage lung cancer (cT1-T3N0, stage IA-IIB) were included in the study. Only 230 satisfied the inclusion criteria. Group bias was reduced through 1:1 propensity score matching, which resulted in 46 patients in each group (open surgery and Uniportal-VATS). RESULTS: Intra-operative and post-operative mortality was null in both groups. There was no difference in post-operative complications (p:1,00) between Uniportal-VATS and open lobectomy. No difference in pathological nodal up-staging was also recorded (11(23.9%) after thoracotomy vs 8(17.4%) after Uniportal VATS, p:0.440). Chest tube duration was longer in open group (p:0.025), resulting in a longer post-operative hospital stay (p:0.08), with a higher post-operative pain (p<<0.001). Additionally, 3-year overall-survival (OS) was 78% after Uniportal-VATS lobectomy vs 74% after open lobectomy (p:0.204), while 3-year disease-specific survival(DSS) was 97% vs 89% (p:0.371), respectively. Three-year disease-free survival (DFS) was 62% in Uniportal-VATS group and 66% in thoracotomy group, respectively (p:0.917). CONCLUSIONS: Uniportal-VATS lobectomy for the treatment of Early-stage lung cancer seems to be a safe and effective technique with similar surgical and short-term survival outcomes as open surgery, but with lower post-operative pain and shorter in-hospital stay.